Incontinentia Pigmenti: A Case Report - Shrestha, R; Kayastha, Bhaskar MM; Reema, Aishath (Journal of Nepal Paediatric Society, 2013)
Incontinentia pigmenti is a rare X-linked dominant condition characterized by abnormalities in skin, eyes, teeth, bones and the central nervous system. A seven year old female child presented to the Dermatology Out Patient Department (OPD) of Bir Hospital with vesicles, bullae, verrucous papules and plaques and hypopigmented streaks on the trunk and extremities of six years duration. Based on the clinical findings she was diagnosed as a case of Incontinentia pigmenti. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7126 J Nepal Paediatr Soc. 2013;33(1):57-60